SUPPORT PROVIDED TO LECTURERS TOWARDS THE IMPLEMENTATION OF INCLUSIVE EDUCATION IN ZIMBABWEAN TEACHERS’ COLLEGES - Madzore, Rosemary; Gasa, Velisiwe (Indonesian Journal of Educational Development (IJED), 2025)
This study explores lecturer support in implementing inclusive education in Zimbabwean teacher colleges. Employing an interpretivist paradigm, a qualitative approach, and a case study design, 24 participants were purposively sampled, including three principals and 21 lecturers. The research drew on Sherman and Wood's classical liberal theory of equal opportunity, focusing on three colleges transitioning to inclusive education. Data were collected through interviews, focus groups, and document analysis, then analysed thematically. Findings reveal insufficient support for lecturers, compounded by non-inclusive infrastructure and a struggling national economy that fails to provide essential teaching resources. The Ministry of Education was found to inadequately assist lecturers in implementing inclusive curricula, leaving them to navigate significant challenges such as a lack of teaching materials. To enhance inclusive education in teacher colleges, the study recommends the provision of assistive aids and personalised learning materials. It also calls for further research to identify effective strategies for implementing inclusive education. These findings highlight the urgent need for systemic improvements to support lecturers and foster equitable educational opportunities.